Fiscal Devolution: A Stepping Stone towards Conflict Resolution in Sri Lanka - Sarvananthan, M. (South Asian Survey, 2012)
Countries afflicted by claims of territorial sovereignty within nation states have been predominantly preoccupied with sharing of administrative and political powers, as in the case of the armed conflict in Sri Lanka. This article argues that fiscal devolution has the potential to empower the regions within contested nation states and thereby contribute to conflict resolution in countries afflicted by internal strife and armed conflict, taking Sri Lanka as a case in point.
Keywords: Conflict resolution; post-war reconstruction; fiscal devolution